2019
DOI: 10.2196/12172
|View full text |Cite
|
Sign up to set email alerts
|

Patient-Sharing Relations in the Treatment of Diabetes and Their Implications for Health Information Exchange: Claims-Based Analysis

Abstract: Background Health information exchange (HIE) among care providers who cooperate in the treatment of patients with diabetes mellitus (DM) has been rated as an important aspect of successful care. Patient-sharing relations among care providers permit inferences about corresponding information-sharing relations. Objectives This study aimed to obtain information for an effective HIE platform design to be used in DM care by analyzing patient-sharing relations among various t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…A web-based interactive visualization of a simplified version of the model on a real regional primary care network is available online (https://csh.ac.at/vis/med_public/pcn-resilience) ( SI Appendix , Text S8). Structural properties of these patient-sharing networks have been reported previously (1114).…”
Section: Resultsmentioning
confidence: 57%
See 1 more Smart Citation
“…A web-based interactive visualization of a simplified version of the model on a real regional primary care network is available online (https://csh.ac.at/vis/med_public/pcn-resilience) ( SI Appendix , Text S8). Structural properties of these patient-sharing networks have been reported previously (1114).…”
Section: Resultsmentioning
confidence: 57%
“…These systems enable analysts to answer questions, such as “Who did what, when, for whom, where and at what costs?,” for practically all medical services in a given country. For instance, in Austria, it has been shown that such data can be used to identify genetic, environmental, and epigenetic disease risks (9, 10) or to investigate how individual health care providers coordinate with each other in the treatment of patients (1114). Health care providers are embedded in multiple formal and informal relationships, because they share information or patients.…”
mentioning
confidence: 99%
“…Previous studies have shown that it is possible to observe the area-level differences or differences by service provider in processes and quality of care by comparing data from EHRs. 9 -12 Data are especially useful when explanatory factors other than health care processes (such as demographic determinants) can be taken into account. Further, the possibility to indicate the changes in processes using health record data from different years is valuable.…”
Section: Discussionmentioning
confidence: 99%
“…It was recently shown that indicators such as the density of care providers fall short of capturing structural barriers to health care that arise from the fact that patients do not access physicians at random 4 . Rather, physicians are embedded in informal and emergent networks of flows of patients between them [5][6][7][8][9][10] . These networks might, for instance, emerge because of geographic proximity, of one physician tending to recommend another one, or due to physicians acting as holiday substitutes to each other, and thereby encode how likely a patient will access a given care provider given that s/he has already accessed a specific other one.…”
Section: Introductionmentioning
confidence: 99%